2008
DOI: 10.1007/s11104-008-9783-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen enrichment lowers Betula pendula green and yellow leaf stoichiometry irrespective of effects of elevated carbon dioxide

Abstract: Elevated carbon dioxide (CO 2 ) and increased nitrogen (N) availability generally increase deciduous tree biomass and alter green and yellow leaf stoichiometry. This paper investigates whether this also applies to Betula pendula (Birch). The effects of elevated atmospheric CO 2 (600 ppmv) and increased N availability (50 and 100 kg N hamonium, nitrate and ammonium nitrate) on net primary production (NPP) and green/yellow leaf C:N of Betula pendula saplings were studied for 3 years. The combination of both fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 71 publications
4
19
0
Order By: Relevance
“…N fertilization significantly increased N concentrations in wheat (Fig. 1 c, d), which was observed in other studies (Ruohomaki et al, 1996;Tomassen et al, 2003;Esmeijer-Liu et al, 2009). At harvest, the grain N and P contents were higher, indicated that N and P in other parts of wheat transferred to the grain.…”
Section: Discussionsupporting
confidence: 85%
“…N fertilization significantly increased N concentrations in wheat (Fig. 1 c, d), which was observed in other studies (Ruohomaki et al, 1996;Tomassen et al, 2003;Esmeijer-Liu et al, 2009). At harvest, the grain N and P contents were higher, indicated that N and P in other parts of wheat transferred to the grain.…”
Section: Discussionsupporting
confidence: 85%
“…Under ambient water conditions, decreased C:Ng and C:Ns in response to N addition were in line with results from other studies (Esmeijer- Liu et al 2009;Novotny et al 2007). Under elevated water conditions, however, N addition showed no eVect on C:Ng and C:Ns.…”
Section: Interactive Evects Of N and Water Additionsupporting
confidence: 92%
“…They can also change in response to global change factors, such as elevated CO 2 concentration (Billings et al 2003), increased N deposition (Esmeijer-Liu et al 2009), decreased biodiversity (Knops et al 2001) and interactions among these factors (Henry et al 2005;Knops et al 2007;Novotny et al 2007). Concurrently, potentially altered precipitation regimes resulting from global climate change may exert strong controls on community composition and ecosystem function of arid and semi-arid areas (Huxman et al 2004;Suttle et al 2007;Bai et al 2008;Gerten et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, plant species diversity generally declines in response to N enrichment (Clark et al 2007). Furthermore, N enrichment will potentially influence plant biomass stoichiometric composition (Esmeijer-Liu et al 2009;Novotny et al 2007), which exerts strong controls on plant growth rate (Niklas et al 2005), ecosystem nutrient use efficiency (Vitousek 1982), litter decomposition (Güsewell and Gessner 2009), herbivory (Hall et al 2007), and several other ecosystem processes. Nevertheless, we still know little about plant stoichiometric responses to the increased N availability.…”
mentioning
confidence: 99%
“…Most previous studies on the responses of plant tissue chemistry and stoichiometry to N enrichment focused on the changes of C and N concentration and C:N ratios (Esmeijer- Liu et al 2009;Knops et al 2007). This may be due to the suggestion that productivity in most ecosystems is limited by N availability (LeBauer and Treseder 2008).…”
mentioning
confidence: 99%